Hacia una conceptualización del Erotismo en Occidente Una mirada filosófica y literaria en torno de la discusión entre cuerpo y alma: Towards a Conceptualization of Eroticism in the West A Philosophical and Literary Look Around the Discussion between Body and Soul - Ortega Oliveros, Mayerlis (Universidad del Zulia, 2021)
The purpose of this article is to show that the conceptualization of eroticism has not allowed the overcoming of the historical dichotomy between the soul and the body, a split that has hampered the understanding of it as a human phenomenon that dimensions man in all his integrality. Because of this, in the first place, a historical-theoretical sketch will be made of the different meanings that eroticism has had, beginning with the philosophical and literary reflections that have arisen in relation to Eros from Greece to the 20th century, in pursuit of to reveal what it is, what it is not and what it could become. Next, it will be evident how eroticism has been approached from two traditional positions that have been mutually exclusive; the moralist or Christian and the immoralist or transgressive, to expose how in each of these positions a perspective of eroticism biased solely as a spiritual or carnal practice has been weighed.